IMPLEMENTATION OF QUANTITATION TECHNIQUES TO PERFORM RGB IMAGE COMPRESSION - Petti Indrayati Sijabat (INFOKUM, 2020)
the use of RGB images is a necessity in various fields. However, its use is constrained by the large file capacity, but it is possible to compress the images that are owned as needed. With the quantization method, the R matrix, G matrix and B matrix will be reduced in level, so that the number of bits used to represent the image is reduced. Because the number of bits is reduced, the file size becomes smaller. The quantization method is included in the Lossy Compression category, so that the compressed image cannot be decompressed again because there is missing information. Image compression is an image compression process that aims to reduce duplication of data in the image so that less memory is used to represent the image than the original image representation. There are factors why the image compression process is very appropriate so that there is no significant correlation between pixels and neighboring pixels